2011
DOI: 10.1186/bcr2937
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of prognostic and predictive value of microtubule associated protein tau in two independent cohorts

Abstract: IntroductionMicrotubule associated proteins (MAPs) endogenously regulate microtubule stabilization and have been reported as prognostic and predictive markers for taxane response. The microtubule stabilizer, MAP-tau, has shown conflicting results. We quantitatively assessed MAP-tau expression in two independent breast cancer cohorts to determine prognostic and predictive value of this biomarker.MethodsMAP-tau expression was evaluated in the retrospective Yale University breast cancer cohort (n = 651) using tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 23 publications
(35 reference statements)
4
26
0
Order By: Relevance
“…Aberrations in many of the above mentioned DUSP4 correlated genes are commonly seen in other types of breast cancer [18-20]. In our study, DUSP4 expression was associated with breast cancer outcomes for non-basal-like TNBC, including those that expressed luminal A or B signature genes.…”
Section: Discussionsupporting
confidence: 57%
“…Aberrations in many of the above mentioned DUSP4 correlated genes are commonly seen in other types of breast cancer [18-20]. In our study, DUSP4 expression was associated with breast cancer outcomes for non-basal-like TNBC, including those that expressed luminal A or B signature genes.…”
Section: Discussionsupporting
confidence: 57%
“…Most of the studies reported that MAPT expression has prognostic value, with high expression associated with favorable patient outcome. However, at the present time, there are few studies indicating that MAPT is a predictive marker for taxane-based chemotherapy (Baquero et al 2011, Smoter et al 2011. We demonstrated that expression levels of MAPT showed positive correlation with expression levels of ER and PgR and negative correlation with expression levels of Ki67, tumor grade, and tumor size in ER-positive breast cancer.…”
Section: Discussionmentioning
confidence: 63%
“…Indeed, compounds that alter MT dynamics are an area of extensive study and several are currently used in the clinic (51). Moreover, recent work even implicates tau in the pathogenesis and prognosis of cancer (52)(53)(54)(55)(56), further supporting this mechanistic link between tau, Hsc70 and MTs. Thus, while isoform selective Hsp70 inhibitors could be best suited for neurodegenerative diseases, it is possible that compounds capable of targeting multiple Hsp70 isoforms could be most advantageous for cancer treatment.…”
Section: Discussionmentioning
confidence: 98%